2002
DOI: 10.2337/diacare.25.11.2053
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of Insulin Aspart and Insulin Lispro in Patients With Type 1 Diabetes

Abstract: OBJECTIVE -Both rapid-acting insulin analogs, insulin aspart and lispro, attenuate prandial glucose excursion compared with human soluble insulin. This trial was performed to study the pharmacokinetic and pharmacodynamic profiles of insulin aspart and insulin lispro in type 1 diabetic patients in a direct comparison and to investigate whether the administration of one analog results in favorable effects on prandial blood glucose control. RESEARCH DESIGN AND METHODS-A total of 24 type 1 diabetic patients (age 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 26 publications
2
83
1
5
Order By: Relevance
“…This effect was negligible in patients in IIT studies. We did not differentiate between the SAI analogues lispro and aspart because it is known that both insulin analogues are equally effective at controlling prandial blood glucose fluctuations in type 1 diabetic patients [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was negligible in patients in IIT studies. We did not differentiate between the SAI analogues lispro and aspart because it is known that both insulin analogues are equally effective at controlling prandial blood glucose fluctuations in type 1 diabetic patients [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…A double-blind, two-period, crossover trial comparing insulin aspart and insulin lispro found no differences between them with regard to maximal insulin concentration, time to half-maximum insulin concentration, and time to 50% decrease of maximum insulin concentration. 23 In a study of obese subjects without diabetes, insulin glulisine and insulin lispro were found to have similar, more rapid time-action profiles compared to human insulin, a difference that prevailed regardless of body mass index and subcutaneous fat thickness. 24 However, in a randomized, double-blind, crossover study on lean to obese subjects without diabetes, insulin glulisine showed a somewhat greater early metabolic action than insulin lispro, an effect that was independent of body mass index and dose.…”
Section: Rapid-acting Analogsmentioning
confidence: 99%
“…En accord avec le profil pharmacodynamique de l'insuline aspart, les données cliniques disponibles montrent que son injection immédiatement avant le repas réduit significativement les oscillations de la glycémie postprandiale, de façon plus importante que l'injection d'insuline 30 minutes avant le repas. Récemment, une comparaison directe de la capacité des formes aspart et lispro à contrôler la glycémie chez des patients diabétiques de type 1 a montré que les deux analogues entraînent une diminution de la glycémie postprandiale (rapport aspart/lispro des Cmax pour les oscillations de la glycémie postprandiale = 1,01) [20]. Deux études réalisées à grande échelle [21,22] ont également montré une diminution faible, mais statistiquement significative, du pourcentage d'HbA1c (environ 0,15% d'HbA1c) après traitement par l'insuline aspart, par rapport à l'insuline humaine.…”
Section: L'insuline Aspartunclassified